2011
DOI: 10.1128/aem.01676-10
|View full text |Cite
|
Sign up to set email alerts
|

Class 1 Integrons, Selected Virulence Genes, and Antibiotic Resistance in Escherichia coli Isolates from the Minjiang River, Fujian Province, China

Abstract: Widespread fecal pollution of surface waters in developing countries is a threat to public health and may represent a significant pathway for the global dissemination of antibiotic resistance. The Minjiang River drainage basin in Fujian Province is one of China's most intensive livestock and poultry production areas and is home to several million people. In the study reported here, Escherichia coli isolates (n ‫؍‬ 2,788) were sampled (2007 and 2008) from seven surface water locations in the basin and evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 42 publications
2
38
1
Order By: Relevance
“…A similar incidence of class 1 integrons in E. coli isolated from wastewater (9.6 %), and surface water of the River Seine, France (11 %) and surface water of the Rio Grande, Mexico (13 %) have been reported previously (Laroche et al, 2009;Ferreira da Silva et al, 2007;Roe et al, 2003). In a study form China, a higher occurrence of class 1 integrons in E. coli isolated from Minjiang River (41 %) was reported however, the authors concluded that the high frequency was probably due to the widespread use of numerous antimicrobial agents in human therapy, livestock, poultry, and fish production in the study area (Chen et al, 2011). High prevalence of E. coli isolates carrying integrons in surface water from China has been reported in a number of studies.…”
Section: Usa 4 % Of the Tetracycline Resistant Isolates Were Positivementioning
confidence: 47%
See 2 more Smart Citations
“…A similar incidence of class 1 integrons in E. coli isolated from wastewater (9.6 %), and surface water of the River Seine, France (11 %) and surface water of the Rio Grande, Mexico (13 %) have been reported previously (Laroche et al, 2009;Ferreira da Silva et al, 2007;Roe et al, 2003). In a study form China, a higher occurrence of class 1 integrons in E. coli isolated from Minjiang River (41 %) was reported however, the authors concluded that the high frequency was probably due to the widespread use of numerous antimicrobial agents in human therapy, livestock, poultry, and fish production in the study area (Chen et al, 2011). High prevalence of E. coli isolates carrying integrons in surface water from China has been reported in a number of studies.…”
Section: Usa 4 % Of the Tetracycline Resistant Isolates Were Positivementioning
confidence: 47%
“…Frequent detection of potential EPEC strains from contaminated marine recreational water in Avalon Bay, California USA has also reported (Hamilton et al, 2010). In another study, about a quarter of the E. coli isolated from Minjiang River in China carried at least one of the 11 virulence genes evaluated (Chen et al, 2011). Similarly, presence of EPEC, EAEC, EIEC, EHEC and ETEC pathotypes has also been reported in sub-tropical surface water collected in Brisbane, Australia (Sidhu et al, 2013).…”
Section: Usa 4 % Of the Tetracycline Resistant Isolates Were Positivementioning
confidence: 86%
See 1 more Smart Citation
“…The abundance, types of resistance, and distribution of resistance in populations of commensal and pathogenic bacteria vary enormously, no doubt due to varied factors, in particular exposure of the enteric flora to antibiotics in human medicine or as commonly employed in commercial animal production (9,10). Emissions of antibiotic residues and resistant bacteria from various human activities, including animal production, fish production, wastewater treatment, and antibiotic manufacturing, will increase the burden of antibiotic resistance in exposed environmental matrices (11)(12)(13)(14)(15)(16). The abundance and the mobility of antibiotic resistance genes in agricultural soils may be enhanced by various management practices, for example, the application of animal manures, wastewater, or waste treatment residues that contain antibiotic resistance genes on mobile elements and antibiotic residues (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…The guidelines were established based on testing of clinical isolates however there are no equivalent standards for environmental isolates. Furthermore, using these standards allows for comparison to other published papers that report results of resistance analysis, including other papers that test environmental E. coli (Reinthaler et al, 2003;Chen et al, 2011;Holvoet et al, 2013;Skariyachan et al, 2015). Five classes of antibiotics commonly used in human medicine were included in the antibiotic resistance testing, including beta-lactams (ampicillin, 10 µg), fluoroquinolones (ciprofloxacin, 5 µg), aminoglycosides (gentamicin, 10 µg), tetracyclines (tetracycline, 30 µg), and sulfonamides (trimethoprim/sulfamethoxazole, 1.25/23.75 µg).…”
Section: Analysis Of Enterococcusmentioning
confidence: 99%